ELEVATED PLUS-MAZE AND THE HOLE BOARD TEST FOR USE AS A QUALITY CONTROL ASSAY OF HERBAL MEDICINES BASED ON PASSIFLORA INCARNATA LINNAEUS - GARCIA, E. B.; PINHEIRO, Y. S. G.; FELIX, N. M.; LOUREIRO, J. M. P.; AMENDOEIRA, F. C.; FERRARIS, F. K. (Ars Veterinaria, 2021)
In the search for the reduction of the side effects caused by allopathy, phytotherapeutic products are already on the veterinary market. This study aimed was to evaluate Elevated Plus-Maze and Hole Board test as an analytical methodology for quality control of anxiolytic medicines based on Passiflora incarnata. The efficacy of three brands commercial differents of Passiflora incarnata extracts was tested in the Elevated Plus-maze (for anxiolytic effect) and the Hole Board test (for locomotor and neophilia activity) in Wistar rats. Treatment with the P. incarnata brands revealed a significant 3-fold increase in the length of stay in the open arms in the LCE. In the ambulation, animals from bands 1 and 3 presented a significant increase, being brand 2 the only one that did not present this relevance. In the neophilia, Passiflora brand 1 presented a significant increase of 3 times and groups 2 and 3 an increase of approximately 2 times. The results showed that different brands of Passiflora have a satisfactory quality standard related to biological activity and showed that the use of Elevated plus-maze/Hole board test can be an effective tool in the quality control of herbal medicines with anxiolytic activity associated with the phytochemical analysis.